2011
DOI: 10.3892/ijo.2011.949
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B7-H3 in hypopharyngeal squamous cell carcinoma as a predictive indicator for tumor metastasis and prognosis

Abstract: Abstract. B7-H3 is a member of the B7 family thought to be a co-regulatory factor of antigen-specific T-cell immune response via co-stimulatory and co-inhibitory receptors. We evaluated its potential expression in head and squamous cell carcinoma (Scc) cell lines, and in clinical tissue samples obtained from 37 patients with human hypopharyngeal Scc. all head and neck Scc cell lines tested expressed both the B7-H3 gene and cell surface protein. the staining intensity of immunoreactivity by tumor cells was blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 24 publications
(36 reference statements)
1
41
0
Order By: Relevance
“…There is no doubt that the B7 family is an important cancer player, thus the B7-H3 study will be very promising in the field of malignancy research. High expression of B7-H3 strengthened the resistance to chemotherapeutics and anti-apoptotic ability, nevertheless knockdown of B7-H3 might enhance the sensitivity of apoptosis induced by drug 34-37. Up to now, many studies had reported that the high-expression of B7-H3 significantly correlated with lymphatic metastasis and lymphangiogenesis in CRC 18,22,23.…”
Section: Discussionmentioning
confidence: 99%
“…There is no doubt that the B7 family is an important cancer player, thus the B7-H3 study will be very promising in the field of malignancy research. High expression of B7-H3 strengthened the resistance to chemotherapeutics and anti-apoptotic ability, nevertheless knockdown of B7-H3 might enhance the sensitivity of apoptosis induced by drug 34-37. Up to now, many studies had reported that the high-expression of B7-H3 significantly correlated with lymphatic metastasis and lymphangiogenesis in CRC 18,22,23.…”
Section: Discussionmentioning
confidence: 99%
“…39 The expression of inhibitory ligands are up-regulated in many cancer types, 16,[40][41][42] and this is linked to poor patient prognosis. 43 However, the mechanistic consequences of this abnormal expression have not been fully defined previously.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported to be a positive regulator for T cell response [8], [9], but later research showed its ability to negatively regulate T cell response, inhibiting T cell proliferation and cytokine secretion [10][13]. Many studies have demonstrated that B7-H3 expression is aberrant on a variety of tumor tissues, with high expression correlated to the progression and poor prognosis for patients with cancer [14][19], suggesting that B7-H3 expression level may be used as a biomarker for cancers [20], [21]. Currently, there are two known isoforms of B7-H3 in humans, 2Ig- and 4Ig-B7-H3.…”
Section: Introductionmentioning
confidence: 99%